Response Surface Methodology for Optimizing Adsorption Process Parameters for Methylene Blue Removal by a Hydrogel Composite - Yi Liu; Yian Zheng; Aiqin Wang (Adsorption Science & Technology)
Response surface methodology was employed to optimize the adsorption parameters of Methylene Blue onto a chitosan- g -poly(acrylic acid)/halloysite hydrogel composite with 50% halloysite content. Such optimization was undertaken to ensure a high efficiency over the experimental ranges employed, and to evaluate the interactive effects of the initial concentration of Methylene Blue, the pH and the temperature on the adsorption process in order to improve the conditions employed in the batch process. A total of 17 adsorption experimental runs were carried out employing the detailed conditions designed by response surface methodology based on the Box–Behnken design. The analysis of variance (ANOVA) indicated that a second-order polynomial regression equation was the most appropriate for fitting the experimental data. The experimental confirmation tests showed a correlation between the predicted and experimental responses (R 2 = 0.9904). The optimal point obtained was located in the valid region and the optimum adsorption parameters were predicted as an initial Methylene Blue concentration of 1034 mg/ℓ, a pH value of 6.1 and a temperature of 41 °C. Under these adsorption conditions, a higher adsorption capacity of 1336.05 mg/g was achieved from a simulated dye solution.